Role of Endothelial Function and Inflammation in Patients with Cardiovascular Risk Factors, with and without a History of Myocardial Infarction - Šebeštjen, Miran; Šabovič, Mišo; Eržen, Barbara; Simčič, Saša; Žegura, Branka; Poredoš, Pavel; Keber, Irena (Cardiology, 2007)
Background: Endothelial dysfunction and inflammation, in particular their lack of improvement after risk reduction, might better reflect advanced atherosclerosis than just the presence of risk factors. The aim of this study was to compare endothelial function and inflammatory parameters in high-risk patients who had no history of myocardial infarction and in patients in a stable phase after myocardial infarction. Methods: We compared endothelial function of the brachial artery, measured using high-resolution ultrasound, in 45 patients with hyperlipidaemia (Group 1), and in 45 patients in a stable period after myocardial infarction (Group 2). Forty-five healthy individuals served as a control group (Group 3). Results: Compared to patients with treated hyperlipidaemia, patients after myocardial infarction had lower values of total and LDL cholesterol (p = 0.015; 0.005) and homocysteine (p < 0.005), but marginally higher IL-6 levels (p = 0.1). Other measurements were comparable. However, flow-mediated dilation of the brachial artery was significantly diminished in patients after myocardial infarction (10.6 ± 3.0; 5.9 ± 4.0; 14.0 ± 1.9% for Groups 1–3; ANOVA p = 0.0001; respectively). Conclusions: We found that patients with previous myocardial infarction have substantially lower endothelial function and increased some inflammatory parameters than patients with a similar level of atherosclerotic risk profile but without clinically evident coronary artery disease.